Lactoferrin for the Prevention of Post-antibiotic Diarrhoea - Laffan, Alison M; McKenzie, Robin; Forti, Jennifer; Conklin, Dawn; Marcinko, Richard; Shrestha, Ruchee; Bellantoni, Michele; Greenough III, William B (Journal of Health, Population and Nutrition, 2012)
Antibiotic-associated diarrhoea (AAD) is a common cause of morbidity and mortality. Older individuals in long-term care facilities are particularly vulnerable due to multisystem illnesses and the prevailing conditions for nosocomial infections. Lactoferrin, an antimicrobial protein in human breastmilk, was tested to determine whether it would prevent or reduce AAD, including Clostridium difficile in tube-fed long-term care patients. Thirty patients were enrolled in a randomized double-blind study, testing eight weeks of human recombinant lactoferrin compared to placebo for the prevention of antibiotic-associated diarrhoea in long-term care patients. Fewer patients in the lactoferrin group experienced diarrhoea compared to controls (p=0.023). Based on the findings, it is concluded that human lactoferrin may reduce post-antibiotic diarrhoea. DOI: http://dx.doi.org/10.3329/jhpn.v29i6.9889 JHPN 2011; 29(6): 547-551